Philippine cargo guide, 1997. (Belgosa Business Communications, 1997)
Contents: Overview of cargo industry. Industry analysis. Industry guidelines. Brief on the Philippines. Seaport maps/schedule, Airport map/schedule. Organizations in the Philippine cargo industry. Product index and directory.